FENOMENA “MARRIAGE IS SCARY” BAGI GEN Z DALAM KONTEN DILAN JANIAR DI TIKTOK - Khoirun Nisa (Jurnal Komunikasi, 2025)
The phenomenon of “Marriage is Scary” that is developing among Generation Z, especially through social media on TikTok. This study aims to determine how the meaning of marriage is formed by Gen Z with the narrative “Marriage is Scary” after being exposed to content from Dilan Janiar’s account with the issue of infidelity, and how symbolic interactions on social media influence perceptions of marriage. This type of research uses a qualitative method with a phenomenological approach and symbolic interactionism theory. With data collection, namely non- participatory observation, interviews, and documentation. The narratives created and analyzed with data reduction, data presentation, and drawing conclusions. Then the data that has been analyzed is then validated with triangulation. The results of this study indicate that TikTok content that displays negative experiences of marriage, such as infidelity and household conflict, becomes a social symbol that influences Gen Z’s perceptions. Gen Z interprets marriage as something full of risk, scary, worrying, and must be considered carefully. In other words, marriage can form a new meaning that marriage becomes something “scary” (Marriage is Scary)